ANALISIS TUNGGAKAN PAJAK KENDARAAN BERMOTOR PADA UNIT PELAYANAN PAJAK DAERAH SAMSAT BANJARMASIN II - Ericha Fadilla; Muhammad Nordiansyah (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2021)
The purpose of this final report research is to determine the receipt of arrears on Motor Vehicle Taxes at the Regional Tax Service Unit Office of SAMSAT Banjarmasin II.The results of this study indicate that the receipt of arrears on Motor Vehicle Taxes at the Regional Tax Service Unit Office of SAMSAT Banjarmasin II has decreased and increased from year to year. The realization of the Motor Vehicle Tax has not been able to reach the target set by the relevant agencies. Arrears on Motor Vehicle Taxes at the Regional Tax Service Unit Office of SAMSAT Banjarmasin II are caused by several reasons from the Taxpayer, namely being busy, forgetting, economic factors, knowledge and old vehicles. Then the efforts made by the Regional Tax Service Unit Office of the Banjarmasin II SAMSAT to reduce the arrears are by opening a Mobile SAMSAT, opening a Drive Thru, making/sending a Warrant to make payments, doing whitening/reasing Motor Vehicle Tax fines, making banners or banners for pay taxes on time, conduct raids twice a month, and conduct counseling at the Regional Tax Service Unit office of SAMSAT Banjarmasin II when the taxpayer pays taxes.